Delinquency in adolescent girls: using a confluence approach to understand the influences of parents and peers - Henneberger, Angela K. (Criminal justice and behavior, 2014)
Determining the interdependence of family and peer influences on the development of delinquency is critical to defining and implementing effective interventions. This study explored the longitudinal relationship among harsh punishment, positive parenting, peer delinquency, and adolescent delinquency using data from a sub-sample of the Pittsburgh Girls Study. Participants were 622 adolescent girls (42% European American, 53% African American); families living in low-income neighborhoods were oversampled. After controlling for the effects of race, living in a single parent household, and receipt of public assistance, harsh punishment and peer delinquency in early adolescence were positively related to delinquency in mid-adolescence. No significant main effects of positive parenting or interaction effects between parenting and peer delinquency were observed. Thus, the effects of harsh parenting and peer delinquency are independent and perhaps additive, rather than interdependent. Results indicate the continued importance of targeting both parenting and peer relationships to prevent delinquency in adolescent girls.